Induktion av persisterande gulkropp hos sto - Santesson, Malin (2005)
This article starts with a review of the literature regarding the normal reproductive physiology of the mare, normal luteolysis, different causes of prolonged luteal phase and theories behind these. The article also presents a study where it was examined if treatment with human choriongonadotropic hormone (hCG) during the luteal phase induces prolonged luteal phase in mares, thus preventing estrus. The study consisted of two parts: one intensive study of eight mares at the former Department of Obstetrics and Gynaecology at SLU, Uppsala, Sweden and one field study of seven mares at a stud farm 70 km north of Uppsala. The mares in the intensive study were divided in two groups: one with four mares that were injected with hCG in luteal phase when they had a follicle of minimum 30 mm and a second group with four mares that were injected with sodium chloride at the same time. These mares were examined with ultrasonography and blood samples. The blood samples were analyzed for progesterone with a solid phase radioimmunoassay. In the field study only two mares were injected with NaCl and the remaining with hCG. These mares were only observed by ultrasonography and only during a short period after treatment.